Impairments in negative emotion recognition and empathy for pain in Huntington's disease families. (February 2015) - Baez, Sandra; Herrera, Eduar; Gershanik, Oscar; Garcia, Adolfo M.; Bocanegra, Yamile; Kargieman, Lucila; Manes, Facundo; Ibanez, Agustin
Abstract: Lack of empathy and emotional disturbances are prominent clinical features of Huntington's disease (HD). While emotion recognition impairments in HD patients are well established, there are no experimental designs assessing empathy in this population. The present study seeks to cover such a gap in the literature. Eighteen manifest HD patients, 19 first-degree asymptomatic relatives, and 36 healthy control participants completed two emotion-recognition tasks with different levels of contextual dependence. They were also evaluated with an empathy-for-pain task tapping the perception of intentional and accidental harm. Moreover, we explored potential associations among empathy, emotion recognition, and other relevant factors – e.g., executive functions (EF). The results showed that both HD patients and asymptomatic relatives are impaired in the recognition of negative emotions from isolated faces. However, their performance in emotion recognition was normal in the presence of contextual cues. HD patients also showed subtle empathy impairments. There were no significant correlations between EF, empathy, and emotion recognition measures in either HD patients or relatives. In controls, EF was positively correlated with emotion recognition. Furthermore, emotion recognition was positively correlated with the performance in the empathy task. Our findings highlight the preserved cognitive abilities in HD families when using more ecological tasks displaying emotional expressions in the context in which they typically appear. Moreover, our results suggest that emotion recognition impairments may constitute a potential biomarker of HD onset and progression. These results contribute to the understanding of emotion recognition and empathy deficits observed in HD and have important theoretical and clinical implications. Highlights: Patients and relatives are impaired in recognizing emotions from isolated faces. Emotion recognition is preserved in both groups when contextual clues are provided. Comprehension of the intentionality of others' actions is compromised only in patients. Empathy ratings are abnormal only in patients. There were no correlations between EF, empathy, and emotion recognition measures.